2022
DOI: 10.1021/acs.biomac.1c01409
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Sugar-Only Polymers with Double-Shoulder Task: Bioactivity and Imaging

Abstract: The search for novel fluorescent materials has attracted the attention of many researchers. Numerous bioimaging materials based on the aggregation-induced emission (AIE) units have been surging and could be employed in wide areas during the past two decades. In recent few years, the appearance of nonconventional fluorescence emitters without aromatic conjugated structures provides another bioimaging candidate which has the advantage of enhanced biodegradability and relatively low cost, and their luminescent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…6a). 47 As a result of the efficient overlap of electron-rich hydroxyl and amide groups with the π electrons and lone-pair electron clouds, these sugar-based polymer nanoclusters have the characteristic of fluorescence emission (Fig. 6b).…”
Section: Synthesis Of Polymers Containing Cyclic Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…6a). 47 As a result of the efficient overlap of electron-rich hydroxyl and amide groups with the π electrons and lone-pair electron clouds, these sugar-based polymer nanoclusters have the characteristic of fluorescence emission (Fig. 6b).…”
Section: Synthesis Of Polymers Containing Cyclic Sugarsmentioning
confidence: 99%
“…42 Chen et al prepared methacryl amide monomer 9b from glucosamine hydrochloride and methacryloyl chloride under the same conditions. [43][44][45][46][47][48] Becer et al reported D-mannose acryl amide monomer 10, 2-(D-mannosyloxy)hydroxyethyl acrylamide, which was synthesized from D-mannose pentaacetate and N-hydroxyethyl acryl amide in the presence of BF 3 •Et 2 O and subsequent deprotection. [49][50][51] Tanaka et al synthesized a series of acryl amide monomers with various triazole-linked sugar groups, such as lactose, 6′-sialyllactose, sialyl N-linked oligosaccharide and maltose.…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, over the past decade, chemical-based information encryption strategies are attracting increasing attention for meeting the challenge of information recording and encryption. Among the relative encryption materials, fluorescent materials have aroused extensive attention due to the intelligence capability to sense, store, analyze, and respond to the external stimuli (solvents, ions, light, molecules, mechanical force, etc. ), making these materials have potential applications in sensors, bioimaging, displays, optical recording, and information security. Meanwhile, fluorescence response endows the luminescent materials with intelligence, which can be displayed by an optical signal output accompanying with the obvious luminescence change such as quenching, enhancement, and emission peak shift toward the external stimuli. Using the fluorescence response mechanism of fluorescent materials toward the external stimuli, chemical-based information security can realize the information storage, encryption, decryption, and anticounterfeiting benefiting from the superior selectivity and unique fluorescence response and therefore strengthen the information security level. In recent years, smart hydrogels, as one of the representative fluorescent materials, are also employed to improve the information security.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, glycobiology has emerged into one of the key fields of research for the development of novel therapeutics. Carbohydrates provide specific interactions in cellular recognition events, in which lectins play a fundamental role. Biologically, lectins are involved in inflammation, virus onset, and cell–cell communication . Therefore, they bear a strong potential as drug targets. …”
Section: Introductionmentioning
confidence: 99%